2023
DOI: 10.1186/s12905-023-02284-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D on the severity of dysmenorrhea and menstrual blood loss: a randomized clinical trial

Abstract: Background Primary dysmenorrhea is considered as one of the women’s main problems during reproductive age. The present study aimed to investigate the effect of vitamin D on the severity of dysmenorrhea and menstrual blood loss. Methods This double-blind, randomized, placebo-controlled trial, was performed on 84 single female college students between 18 and 25 years old who living in dormitories. Students with primary dysmenorrhea and vitamin D defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 24 publications
0
11
0
3
Order By: Relevance
“…As the duration of the menstrual cycle ranged from 21 to 35 days, as one of the inclusion criteria, our analysis of the study duration time was divided into two groups: over or under 70 days (two cycles). Various dose intervals for each regimen were found, including once in the study period (2/9) [ 20 , 23 ], monthly (3/9) [ 9 , 16 , 17 ], weekly (3/9) [ 18 , 21 , 22 ], and daily (1/9) [ 19 ]. Using the Endocrine Society’s Definition of vit.…”
Section: Discussionmentioning
confidence: 99%
“…As the duration of the menstrual cycle ranged from 21 to 35 days, as one of the inclusion criteria, our analysis of the study duration time was divided into two groups: over or under 70 days (two cycles). Various dose intervals for each regimen were found, including once in the study period (2/9) [ 20 , 23 ], monthly (3/9) [ 9 , 16 , 17 ], weekly (3/9) [ 18 , 21 , 22 ], and daily (1/9) [ 19 ]. Using the Endocrine Society’s Definition of vit.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Amzajerdi et al . [ 25 ] reported that high-dose Vitamin D supplementation (300,000 IU/day) significantly decreased the VAS and VMS scores for dysmenorrhea over two months. A systematic review reported significantly reduced dysmenorrhea after vitamin D and calcium supplementation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A secondary objective involved examining the correlation between vitamin D levels and dysmenorrhea severity using Pearson's correlation analysis. The VAS, a 10-point scale (0=no pain, 10=worst pain) [ 24 ], and the VMS, a 4-point scale (ranging from no pain to severe pain) [ 25 ], were employed to evaluate dysmenorrhea severity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D deficiency has been reported to induce or exacerbate dysmenorrhoea symptoms [14]. Notably, several randomised controlled trials (RCTs) have demonstrated that vitamin D supplementation reduces pain intensity in patients with dysmenorrhoea; thus, this may be an alternative treatment option for dysmenorrhoea [15][16][17][18][19][20][21][22]. However, other studies have reported limited effects [23][24][25].…”
Section: Introductionmentioning
confidence: 99%